2021
DOI: 10.1111/ejss.13107
|View full text |Cite
|
Sign up to set email alerts
|

Untrafficked furrowed seedbed sustains soil physical quality in sugarcane mechanized fields

Abstract: Management strategies that reduce machinery traffic, such as creating seedbeds, could be adopted to preserve soil health and reduce soil physical restriction to sugarcane (Saccharum sp.) growth. Field experiments on clayey and sandy loam soils were conducted along four crop seasons (2013–2017) to investigate the changes in bulk density, soil penetration resistance, macroporosity and microporosity in the row and inter‐row positions, as well as sugarcane biomass production (root and stalk yield) under different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…For sugarcane, lime application is based on guidelines from regional bulletins calibrated to conventional soil tillage and burned-harvest systems [15]. Although conventional soil tillage remains the primary form of sugarcane tillage management, the advent of GPScontrolled machinery traffic has opened new possibilities for soil tillage systems, including localized tillage management [16,17]. In addition, green harvest methods, i.e., harvest without burning, are gaining ground in Brazil.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For sugarcane, lime application is based on guidelines from regional bulletins calibrated to conventional soil tillage and burned-harvest systems [15]. Although conventional soil tillage remains the primary form of sugarcane tillage management, the advent of GPScontrolled machinery traffic has opened new possibilities for soil tillage systems, including localized tillage management [16,17]. In addition, green harvest methods, i.e., harvest without burning, are gaining ground in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…To enable deeper lime placement, sugarcane producers are increasingly adopting localized tillage management, such as deep strip-tillage on planting furrows, reserving inter-rows specifically for machinery traffic. However, the few available studies have primarily focused on soil physical evaluations and operational efficiency [16,17,[20][21][22][23][24] rather than soil chemical fertility and soil acidity management. Addressing this gap is important, as chemical impediments can reduce the exploration of deeper layers by the plant root system, particularly in acidic soils [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have reported similar bulk density increase and macroporosity reduction in soils under sugarcane without straw removal (i.e., all the straw kept on the soil surface), especially at the end of the cultivation cycle, after five to six years of machinery traffic [42,57,58]. Other management practices, such as controlled traffic and or double row spacing [59][60][61][62], and reduced tillage [47,63] seem to have a higher impact on the mitigation of soil structural and physical degradation. In addition, in a recent study, Cherubin et al [64] concluded that the "damper" effect of sugarcane straw left on the soil surface is very subtle (i.e., increased 15 kPa in soil load-bearing capacity), and is thus presumably insufficient to diminish the risk of soil compaction caused by successive stresses promoted by heavy machinery traffic along the sugarcane production cycles.…”
Section: Impact Of Straw Removal On Physical and Hydraulic Indicatorsmentioning
confidence: 89%
“…Nevertheless, we did not detect the direct influence of straw removal on the loss of function and service provision. The main driver for degradation appears to be compaction caused by heavy machinery traffic throughout the years of cultivation [42,62]. In addition, straw removal seems to have less impact on soil functions in clayey soils when compared to sandy soils, as soil organic matter has more influence on the hydraulic parameters of sandy soils as opposed to clays [78].…”
Section: Soil Water Flow Regulation Under Straw Removal Managementmentioning
confidence: 99%
“…Mechanized harvesting leaves sugarcane straw on the soil surface, which is expected to enhance soil macrofauna over the years and improve soil physical quality (Barbosa et al, 2019(Barbosa et al, , 2021Castioni et al, 2018;Tenelli et al, 2019). Indices such as MWD and WAD are used to evaluate aggregate stability, with higher values indicating better stability (Yan et al, 2020).…”
Section: Soil Physical Propertiesmentioning
confidence: 99%